Automated tax-control system, in local governments - Rodríguez Mateo, Víctor Adolfo (2018)
The municipal administration in Peru is part of the national policy of modernization of public management to 2021. The SUNAT, RENIEC, ONPE and SAT are known by their efficient management results. The problem is that there are municipalities with tax-administration systems that are very limited in their functions. The “Automated System of Control of Tax Values (SACVT)” is a solution presented in this research, of descriptive and explanatory type with the objective of determining the way in which the application of this system would influence the administrative tax management of the District Municipality of San Luis, source of the investigation. For which a transversal correlative analysis was carried out and surveys were applied to elucidate the analyzed variables such as the Automated System and the Administrative Tax Administration. This was applied to the officials and technicians related to the income management of the Municipality. The result obtained, confirmed the hypothesis, that the impact of the system application is significant for a better municipal tax management. Considering that the municipal administration in Peru is part of the national policy of modernization of public management to 2021, and knowing the efficiency of the systems of SUNAT, RENIEC, ONPE and SAT, the research proposed solutions for the deficient automated systems in the municipality.